(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This study examines the linguistic features of reporter speech in English media discourse from a pragmalinguistic and discourse-analytical perspective. The primary objective is to identify the key linguistic and communicative strategies employed by journalists to convey information while simultaneously influencing audience perception. The research focuses on lexical, semantic, and discursive mechanisms, including evaluative language, framing, legitimization, and authority appeal. The findings demonstrate that reporter speech in English media discourse functions not only as a means of information transmission but also as a powerful tool for shaping public opinion and constructing social reality.